Risky riding and its correlates in two-wheeler riding young men: Pillion riders' perspective - Rajesh Kumar; Seema Mehrotra; Rajeev J Michael; Humera Banu; Paulomi M Sudhir; Manoj K Sharma (Wolters Kluwer Medknow Publications, 2020)
Background: Risky riding is one of the major contributing factors in road fatalities. The present study aimed to explore the risky riding behaviors and its correlates in two-wheeler riding young men, as ascertained from pillion riders' perspective. Materials and Methods: A survey that captured perspective of pillion riders about two-wheeler riding young men with whom they used to pillion ride most frequently was administered on 115 subjects. The survey consisted of items pertaining to risky riding, perceived impact of negative emotion on riding, expression of negative emotion on roads in response to frustrating situations, road traffic accidents, and pillions' strategies to reduce anger/stress in their two-wheeler riders. Results: Two-wheeler riders who comprised young men were categorized into two groups: (i) high-risk riding group (n = 54 [48%]) and (ii) low-risk riding group (n = 61 [52%]) based on the subjective report of risky riding behaviors by their pillion riders. The results showed that negative emotions were perceived to have adverse influence on riding in persons with high-risky riding. Pillion riders reported that two-wheeler riding young men with high-risky riding expressed more aggressive behaviors (verbal and nonverbal) while riding in response to frustrating situations and also experienced near misses and minor accidents more frequently than their counterparts. Pillion riders reported utilizing various strategies to regulate emotions and behaviors of two-wheeler riders. Conclusions: The present study highlights assessing risky riding and their correlates from pillion riders' perspective and strengthening their positive influence on two-wheeler riding. It has significant implications in minimizing risky behaviors on roads and enhancing road safety.